Variations on an ordering theme with constraints - Guttmann, Walter (2006)
We investigate the problem of nding a total order of a nite set that satis es various local ordering constraints. Depending on the admitted constraints, we provide an e cient algorithm or prove NP-completeness. We discuss several generalisations and systematically classify the problems